2021
DOI: 10.1039/d0an02200d
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective simultaneous determination of Cu(ii), Co(ii), Ni(ii), Hg(ii), and Mn(ii) in water samples using microfluidic paper-based analytical devices

Abstract: A new paper-based analytical device design was fabricated by wax printing method for simultaneous Cu(II), Co(II), Ni(II), Hg(II), and Mn(II) determination. Colorimetry was used to quantify the heavy metal ions,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…On the other hand, some applications as the analytical photometric determination of traces of Ni, Pd or Pt [32,35,52] or their use in (medical) coordination chemistry [52][53][54][55][56] seem to make use of the properties of the molecular units and UV-vis absorption spectra of [Ni(Hdmg)2] in solution have been discussed as to stem from monomolecular units [15,16,46,57]. However, other spectroscopic data from species in solution is not reported and the frequently reported virtual insolubility of the materials sheds doubts on the question of the monomolecular species cause the absorptions of [Ni(Hdmg)2] [15,16,52,57] and are responsible for the biological effects of [Ni(Hdmg)2] [53] and [Pt(Hdmg)2] [54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some applications as the analytical photometric determination of traces of Ni, Pd or Pt [32,35,52] or their use in (medical) coordination chemistry [52][53][54][55][56] seem to make use of the properties of the molecular units and UV-vis absorption spectra of [Ni(Hdmg)2] in solution have been discussed as to stem from monomolecular units [15,16,46,57]. However, other spectroscopic data from species in solution is not reported and the frequently reported virtual insolubility of the materials sheds doubts on the question of the monomolecular species cause the absorptions of [Ni(Hdmg)2] [15,16,52,57] and are responsible for the biological effects of [Ni(Hdmg)2] [53] and [Pt(Hdmg)2] [54].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure experiments have shown that the M ... M interactions account also for the compressibility of these structures and the pressure-dependent changes of colour and electronic properties [3,4,8,12,[26][27][28][29][30][31]. These virtually insoluble metal ... metal stacked solids are the basis for applications of the three compounds [M(Hdmg) 2 ] (M = Pt, Pd, Ni) for the extraction or removal of these elements [32][33][34][35], as components of solid catalysts [36][37][38][39][40], as solid but easily evaporable precursors [37][38][39][40][41][42][43][44][45][46][47], and in optical devices (e.g., pressure calibrants/indicators) [3,4,12,[26][27][28][29][30][31][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…and pond samples were analysed and gave good accuracy and agreement with an ICP-OES method [83]. Grasianto et al recently reported the use of bathophenanthroline nanocrystals loaded onto a μPAD.…”
Section: Fluorescence Detectionmentioning
confidence: 93%
“…The linear ranges were 0.32-63.55 mg L −1 Cu(II), 0.59-4.71 mg L −1 Co(II), 5.87-352.16 mg L −1 Ni(II), 0.20-12.04 mg L −1 Hg(II), and 0.11-0.55 mg L −1 Mn(II). Samples of drinking water and pond samples were analysed and gave good accuracy and agreement with an ICP-OES method [83]. Grasianto et al recently reported the use of bathophenanthroline nanocrystals loaded onto a µPAD.…”
Section: Absorbance Based Detectionmentioning
confidence: 98%
“…There is a pressing need to develop alternative and inexpensive methods that permit on-site detection of metal ions. More recently, a microfluidic paper-based analytical device (mPAD) has been designed for quantifying metals in water, and the detection limit for copper and zinc can be as low as 0.1 ppm (8,9). With the advancement of synthetic biology, there is an emerging interest in developing field-deployable "biosensors" for water quality monitoring (10).…”
Section: Introductionmentioning
confidence: 99%